Balto - Wells, Simon; Ruby, Cliff; Bacon, Kevin, 1958-; Fonda, Bridget; Collins, Phil.; Horner, James; Universal Pictures (Firm); Universal Home Video (Universal City, CA : Universal Home Video, 1998)
Balto, a sled dog in Alaska, makes an arduous journey to bring life-saving medicine to a town during a diphtheria epidemic.
Animated.
Originally released as a motion picture in 1995.
Director of photography, Jan Richter-Friis; production design, Hans Bacher; editor, Sim Evan-Jones, Nick Fletcher; music, James Horner.
Featuring the voices of Kevin Bacon, Bridget Fonda, Phil Collins, Bob Hoskins.
MPAA rating: G.
VHS Hi-fi stereo surround.
Keywords: Dogs -- Drama; Human-animal relationships -- Drama; Animated films; Films for the hearing impaired; Dogs -- Fiction; Feature films